A Parent-Based Intervention to Reduce Sexual Risk Behavior in Early Adolescence: Building Alliances Between Physicians, Social Workers, and Parents - Guilamo-Ramos, Vincent; Bouris, Alida; Jaccard, James; Gonzalez, Bernardo; McCoy, Wanda; Aranda, Diane (Journal of adolescent health, 2011)
To evaluate the efficacy of a parent-based intervention to prevent sexual risk behavior among Latino and African American young adults. This was delivered to mothers while waiting for their adolescent child to complete an annual physical examination. A randomized clinical trial was conducted with 264 mother–adolescent dyads in New York City. Adolescents were eligible for the study only if they were African American or Latino and aged 11–14 years, inclusive. Dyads completed a brief baseline survey and were then randomly assigned to one of the following two conditions: (1) a parent-based intervention (n = 133), or (2) a “standard care” control condition (n = 131). Parents and adolescents completed a follow-up survey nine months later. The primary outcomes included whether the adolescent had ever engaged in vaginal sexual intercourse, the frequency of sexual intercourse, and the frequency of oral sex. Relative to the control group, statistically significant reduced rates of transitioning to sexual activity and frequency of sexual intercourse were observed, with oral sex reductions nearly reaching statistical significance ( p < .054). Specifically, sexual activity increased from 6% to 22% for young adults in the “standard of care” control condition, although it remained at 6% among young adults in the intervention condition at the 9-month follow-up. A parent-based intervention delivered to mothers in a pediatric clinic as they waited for their child to complete a physical examination may be an effective way to reduce sexual risk behaviors among Latino and African American middle-school young adults.